2013
DOI: 10.1111/rda.12000
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Promotes Mouse Pre‐implantation Development: Involvement of Calcium Mobilization and P38 Mitogen‐Activated Protein Kinase Activation

Abstract: The study was designed to examine the effects of calcitonin (CT) on the development of murine pre-implantation embryos and possible molecular mechanisms involved in the process. In the present study, the 2-cell embryos were treated with different concentration of CT in vitro for the indicated time and the results demonstrated that CT promoted the development of the pre-implantation embryos in a dosage-dependent manner by increasing the intracellular Ca(2+) level. Furthermore, the present study showed that CT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Although the physiological importance of CT in systemic Ca 2+ homeostasis in mammals is controversial [42], the function of CT as a paracrine factor in the female reproductive tract has been suggested [24,25,26]. The expression of CTR mRNA in murine preimplantation embryos has been reported [24], and CT can increase intracellular Ca 2+ levels by activating CTR [24, 25, 43, 44]. Therefore, we examined the expression of CTR mRNA in bovine preimplantation embryos and the effects of CT treatment on the in vitro development of embryos that had been heat shocked.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the physiological importance of CT in systemic Ca 2+ homeostasis in mammals is controversial [42], the function of CT as a paracrine factor in the female reproductive tract has been suggested [24,25,26]. The expression of CTR mRNA in murine preimplantation embryos has been reported [24], and CT can increase intracellular Ca 2+ levels by activating CTR [24, 25, 43, 44]. Therefore, we examined the expression of CTR mRNA in bovine preimplantation embryos and the effects of CT treatment on the in vitro development of embryos that had been heat shocked.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Wang et al [25] reported that the P38MAPK pathway is partially involved in the enhancing effects of CT on murine preimplantation development in vitro . Therefore, it cannot be excluded that the heat shock-ameliorating effect of CT on bovine preimplantation embryos is also mediated by signal transduction pathways like this that are independent of Ca 2+ signaling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations